Hydroxyl-group-modified polymeric carbon nitride with the highly selective hydrogenation of nitrobenzene to N-phenylhydroxylamine under visible light. Issue 10 (26th April 2021) - Pei, Linjuan; Tan, Hao; Liu, Meixian; Wang, Ruiyi; Gu, Xianmo; Ke, Xuebin; Jia, Jianfeng; Zheng, Zhanfeng
Abstract : The –OH modification over carbon nitride alters the selectivity of photocatalytic nitrobenzene hydrogenation to the intermediate, N -phenylhydroxylamine. Abstract : Regulating the surface properties of catalysts to control the selectivity of a reaction is a fascinating approach. Bulk polymeric carbon nitride exhibits a poor N -phenylhydroxylamine yield in nitrobenzene reduction reaction mainly due to the uncontrollable condensation side reactions. Thus, adjusting the structure of the catalyst was key to solving the above issue. Herein, –OH groups-modified polymeric carbon nitride was prepared via a simple hydrothermal treatment. With the introduced –OH groups replacing the terminal amino groups (–NH2 ) at the surface of the polymeric carbon nitride, a 3-fold increase in reaction rate was achieved, along with a high selectivity toward N -phenylhydroxylamine ( ca. 80%). The introduced –OH group was found to be beneficial to the adsorption of the nitrobenzene, based on the density functional theory (DFT) calculation. It could also lower the recombination rate of photoinduced electron–hole pairs, which would accelerate the photocatalytic oxidation of isopropanol and supply more protons to participate in the hydrogen-transfer process. Moreover, the elevated conduction band position after –OH modification would provide high energetic photogenerated electrons to promote the reduction of nitrobenzene. These are all important to guarantee the highly selective production of N -phenylhydroxylamine. This paper not only provides a simple and green approach for the modification of polymeric carbon nitride toward an efficient photocatalyst, but also sheds light on the further study of the selective hydrogenation.